The Dynamics of Islamic Education Politics and Their Implications for the Merdeka Curriculum Policy in Islamic Higher Education Institutions - Nurul Aisah Samosir; Ahmad Arifi (Yayasan Rahmat Islamiyah, 2026)
This study analyzes the dynamics of Islamic education policy in Indonesia and its implications for the implementation of the Merdeka Curriculum through the Merdeka Belajar-Kampus Merdeka (MBKM) policy in Islamic higher education institutions. Using a qualitative approach based on literature review, this article examines the historical, regulatory, and political developments that have influenced the direction of Islamic education from the pre-independence period to the reform era. The results of the study show that political configurations have a significant influence on the formation of the identity, structure, and orientation of Islamic education, especially in terms of curriculum standardization, institutional transformation, and the expansion of academic autonomy. The implementation of the Independent Curriculum in Islamic higher education presents both opportunities and challenges, such as the need to maintain a balance between academic freedom and Islamic epistemology, strengthening lecturer competencies, and managing external partnerships in an ethical and visionary manner.